IMPORTANCE OF WRITING SKILLS FOR PRIMARY EDUCATION - Nosirova Ruxshona Asliddin qizi,; Razzaqova Shahlo Baxtiyor qizi, (TADQIQOTLAR, 2025)
Abstract:Writing  skills  are  a  fundamental  component  of  primary  education, forming the basis for students’ future academic and personal development. At the early stages of learning, writing helps children organize their thoughts, improve hand–eye coordination, and develop essential language abilities such as vocabulary, grammar, and  sentence  structure.  Strong  writing  skills  also  support  reading  comprehension, critical thinking, and effective communication. Furthermore, early exposure to writing encourages creativity and allows young learners to express their emotions, ideas, and experiences  more  confidently.  As  education  becomes  increasingly  digital,  writing remains  a  vital  tool  for  learning  across  subjects  and  for  building  lifelong  literacy. Therefore, strengthening writing instruction in primary schools is essential for ensuring students’ long-term educational success.